Controlling Light to Optimize Growth and Added Value of the Green Macroalga Codium tomentosum - Marques, Rúben; Moreira, Anthony; Cruz, Sónia; Calado, Ricardo; Cartaxana, Paulo (Frontiers in Marine Science, 2022)
Codium tomentosum is a recently domesticated green macroalga, being currently cultured as an extractive species in integrated multi-trophic aquaculture (IMTA). Optimization of light requirements in outdoor systems must be achieved to increase the market value of cultivated algal biomass. The present study addresses the seasonal effects of light intensity and wavelength on productivity, pigment composition and epiphyte overgrowth in C. tomentosum cultured in a land-based IMTA system. Exposure to high light (non-filtered sun light) lead to higher net productivities in spring. However, non-filtered sun light caused significantly reduced productivities during summer when compared to filtered sun light (~ 4x lower irradiance levels). Furthermore, lower photosynthetic capacity (Fv/Fm) was observed in macroalgae cultured under high light during summer, indicating photoinhibition. Treatments with filtered sun light (low and red light) showed intermediate and more stable productivities. Epiphyte biomass was higher under high light and the lowest epiphyte overgrowth was recorded under red light. Concentrations of light-harvesting pigments were lower in summer than in spring, indicating a seasonal photoacclimation of macroalgae. An opposite seasonal trend was observed for accessory xanthophylls, as the main role of these pigments is photoprotection. Higher all-trans-neoxanthin and violaxanthin concentrations were found in high light than in low or red light treatments, confirming the important role of these biomolecules in the photoprotection of C. tomentosum. This study underlines the importance of controlling light to optimize algal growth outdoors and enhance the production of high-value compounds (i.e., pigments). Additionally, this practice can also reduce epiphyte overgrowth, thus enhancing the valorization of macroalgal biomass derived from C. tomentosum aquaculture.